2016
DOI: 10.1152/ajpheart.00751.2015
|View full text |Cite
|
Sign up to set email alerts
|

Exercise training improves vascular mitochondrial function

Abstract: Exercise training is recognized to improve cardiac and skeletal muscle mitochondrial respiratory capacity; however, the impact of chronic exercise on vascular mitochondrial respiratory function is unknown. We hypothesized that exercise training concomitantly increases both vascular mitochondrial respiratory capacity and vascular function. Arteries from both sedentary (SED) and swim-trained (EX, 5 wk) mice were compared in terms of mitochondrial respiratory function, mitochondrial content, markers of mitochondr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
32
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(39 citation statements)
references
References 53 publications
(64 reference statements)
5
32
1
1
Order By: Relevance
“…However, in contrast to some previous reports investigating the effects of exercise on arterial mitochondria [2728, 4042] we did not observe an increase in arterial mitochondrial respiratory protein content with voluntary aerobic exercise. The lack of increase in mitochondrial protein content that we observed may be attributable to the nature of the exercise intervention, as voluntary wheel running—an intermittent stimulus—is distinctly different than the forced, continuous treadmill and swimming exercise paradigms employed in previous investigations.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…However, in contrast to some previous reports investigating the effects of exercise on arterial mitochondria [2728, 4042] we did not observe an increase in arterial mitochondrial respiratory protein content with voluntary aerobic exercise. The lack of increase in mitochondrial protein content that we observed may be attributable to the nature of the exercise intervention, as voluntary wheel running—an intermittent stimulus—is distinctly different than the forced, continuous treadmill and swimming exercise paradigms employed in previous investigations.…”
Section: Discussioncontrasting
confidence: 99%
“…However, given that vascular mitochondria are particularly critical for intra- and inter- cellular signaling functions [1012], mitochondria in both vascular cell types are likely important for regulation of arterial endothelial function. In addition to our finding that preserved arterial resilience with exercise is accompanied by improvements in whole artery mitochondrial health, previous work has also demonstrated that alterations in whole artery and VSMC mitochondrial health with aging, disease and exercise are accompanied by corresponding changes in endothelial function [1314, 2728, 4042]. …”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…The qPCR data were obtained from five different samples in triplicate. Calculations of relative normalized gene expression were performed according to the ΔCt method as described before (7). The data were normalized to housekeeping gene, 18S ribosomal RNA.…”
Section: Reverse Transcription-quantitative Polymerase Chain Reactionmentioning
confidence: 99%
“…The combination of abnormal eating habits and a sedentary lifestyle increase the risk factors of obesity and CVD (6). A previous study has demonstrated that exercise improves vascular function by increasing the vascular mitochondrial respiratory capacity, bioavailable nitric oxide (NO), and redox balance in a sedentary rodent model (7). While prolonged sitting in humans prompts leg endothelial dysfunction, fidgeting improves leg endothelial and vascular function through the intermittent increases in vascular shear stress (8).…”
Section: Introductionmentioning
confidence: 99%